VD_FINDINFO Jug / 2021 / 30 vom 14. August 2020 - VD Tribunal cantonal (2020)
APPROPRIATION ILLÉGITIME, ERREUR SUR LES FAITSDROIT PÉNAL, ORDONNANCE PÉNALE, ADMISSION DE LA DEMANDE | 13 CP, 137 ch. 2 CP, 353 CPP (CH), 9 CPP (CH)